ECONOMIC INTERESTS OF UKRAINE: PROBLEMS OF DEFINITION AND IMPLEMENTATION IN THE CONTEXT OF INNOVATION RENEWAL (CIS VECTOR) - Nyzhnyk, Yuliia (Journal of European Economy, 2017)
The paper is concerned with the problem of integrity and coherence of foreign economic policy of Ukraine from the view of priority of innovation model development. On the example of interrelations with the CIS countries ambiguity is demonstrated, and thus, the challenges faced for the implementation of Ukrainian economic interests in this given context. The key problematic issues are defined, which are faced on the way for effective trade and economic cooperation with the CIS, and a series of actions are offered to solve them. The algorithm is formulated for correct definition and implementation of economic interests of Ukraine in the global environment.